Analisis Kesalahan Siswa dalam Menyelesaikan Soal Matematika Materi Sistem Persamaan Linier Dua Variabel Ditinjau dari Segi Kognitif - Indasari; Choirul Kurniawan (Universitas Insan Budi Utomo, 2022)
Results of observations made at MTs Islamiyah Sukopuro, in that school there are problems in solving math problems on SPLDV material from a cognitive perspective. In accordance with what was conveyed by the mathematics subject teacher for grade 8A, in the ongoing learning process it was found that the students' understanding of the material was low. This is indicated by the teacher giving questions to students, and not a few students make mistakes when working on these questions. The mistakes made by students include not understanding the meaning of the problem, errors in counting, errors in mastering formulas and mathematical concepts. So the purpose of this study is to describe the problems in students' errors in solving mathematics problems in SPLDV material in terms of cognitive and describe efforts to increase student understanding in SPLDV material in terms of cognitive. The method in this study used a qualitative descriptive method. This research was conducted at MTs Islamiyah Sukopuro, Jabung district, Malang district. The subjects in this study were grade 8A MTs Islamiyah Sukopuro. This study uses tests and interviews in the data collection process. The results of this study used tests and interviews in the data collection process. Based on the results of data analysis, this study can conclude that students' errors are reading problems, misunderstanding problems, incorrect procedures, missing conclusions, conceptual errors, drawing conclusions, language interpretation errors, calculation or computational errors, less thorough, hasty attitude.